IR and IGF-1R expression affects insulin induced proliferation and DNA damage. (March 2017) - Othman, Eman Maher; Altabaa, Tahanee; Hintzsche, Henning; Stopper, Helga
Abstract: Diabetes mellitus type 2 is in its prediagnostic and early phase characterized by hyperinsulinemia. Previously, we pointed out hyperinsulinemia as a potential link between diabetes mellitus and the increased cancer risk that is associated with this disease through its induction of oxidative stress and DNA damage. In the present study, we address the relationship between the induction of proliferation and genomic damage in vitro in cell lines with different expression of the insulin and the IGF-1 receptors after treating the cells with insulin and the insulin analog glargine. Contribution of the IGF-1 receptor was further examined by application of the IGF-1R inhibitor ((5R, 5aS, 8aR, 9R)-9-hydroxy-5, 8, 8a, 9-tetrahydro-5-(3, 4, 5-trimethoxyphenyl)-furo[3_, 4_:6, 7]-naphtho[2, 3- d ]-1, 3-dioxol-6(5aH)-one) (PPP). Insulin as well as insulin glargine stimulated cell proliferation in IGF-receptor-dominated MCF-7 cells and not in insulin receptor-dominated BT-474 cells and PPP attenuated this effect. Both insulins induced DNA damage which was reduced by PPP in MCF-7 cells only. Overall, we showed in this study that high levels of insulin and insulin glargine can enhance cell proliferation in cells which highly express IGF-1 receptor and induce DNA damage in cells with high and also in those with low IGF-1 receptor levels. Highlights: Diabetic patients have higher cancer risk in comparison with healthy individuals. Insulin and insulin glargine stimulate proliferation and induce DNA damage. IR and IGF-1R expression level affect insulin-induced proliferation and DNA damage. Hyperinsulinemia could increase cancer risk in diabetic patients.